2013
DOI: 10.1002/ajim.22284
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide exposures to migrant farmworkers in eastern NC: Detection of metabolites in farmworker urine associated with housing violations and camp characteristics

Abstract: Background The purpose of this paper is to present and evaluate descriptively bivariate associations between urinary metabolites of pesticides and herbicides and migrant camp conditions, violations and personal worker behaviors at home for farmworkers who do not apply pesticides. Methods We studied 183 migrant farmworker camps in eastern North Carolina in 2010. Data and urine samples were collected from 371 men. Predictor measures included violations in six domains of housing regulations and nonviolation cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
19
5
Order By: Relevance
“…In addition, similar TCPY concentrations were reported in another study from North Carolina in male migrant tobacco workers who did not participate in any pesticide application processes [41]. Parathion metabolite, PNP, concentrations detected in our study were equivalent to the concentrations found in Thailand by Panuwet et al [39], but lower than the concentrations found by Raymer et al [41] in North Carolina.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, similar TCPY concentrations were reported in another study from North Carolina in male migrant tobacco workers who did not participate in any pesticide application processes [41]. Parathion metabolite, PNP, concentrations detected in our study were equivalent to the concentrations found in Thailand by Panuwet et al [39], but lower than the concentrations found by Raymer et al [41] in North Carolina.…”
Section: Discussionsupporting
confidence: 89%
“…However, Aldana-Madrid et al [32] studied local field workers from Sonora, which are not representative of our study population, that frequently migrate from the Southern Mexican States and temporarily reside in migrant dormitories located within the farm where they are employed. Interestingly, when comparing our OP results with other farmworker pesticide studies outside of the Sonora region, we found that concentrations of the chlorpyrifos metabolite (TCPY) in our study participants were higher than those reported in studies conducted in Ecuador, Thailand, and a study conducted in Latino farmworkers from North Carolina [38,39,41]. In addition, similar TCPY concentrations were reported in another study from North Carolina in male migrant tobacco workers who did not participate in any pesticide application processes [41].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Research with Latino tobacco workers in North Carolina documents that these workers are exposed to large numbers of pesticides, often with large doses. [30][31][32][33] These include organophosphorus, carbamate, and pyrethroid pesticides, all of which are neurotoxic. Exposure to the organophosphorus and carbamate pesticides is reflected in depressed cholinesterase levels.…”
Section: Discussionmentioning
confidence: 99%
“…About 20% lived in households with more than eight workers shower and about 20% lived where not met the standard of 30 or fewer workers per washing machine. RAYMER et al (2014) studied 183 migrant farmworker camps in eastern North Carolina in 2010. Data and urine samples were collected from 371 men.…”
Section: Rural Workers' Health and The Use Of Pesticides In Developedmentioning
confidence: 99%